2020
DOI: 10.1186/s13098-020-00583-7
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone in the era of COVID-19: friend or foe? An essay on the effects of dexamethasone and the potential risks of its inadvertent use in patients with diabetes

Abstract: Background The disclosure in the media of a benefit with the use of dexamethasone in patients with COVID-19 infection sets precedents for self-medication and inappropriate use of corticosteroids. Methods This is a critical interpretive synthesis of the data available in the literature on the effects of the use of corticosteroids and the impact that their indiscriminate use may have on patients with diabetes. Reviews and observational and experimental studies published until June 18, 2020 were selected. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 93 publications
1
63
0
18
Order By: Relevance
“…However, the same trial found that there was a modest detrimental effect in patients not receiving respiratory support, again highlighting the importance of appropriate balance in the inflammatory response to COVID-19. In patients with diabetes, corticosteroids can have an impact on glycaemic control and other metabolic parameters and their use should be under careful clinical review ( 303 ).…”
Section: Key Factors In the Interplay Between Covid-19 And Diabetesmentioning
confidence: 99%
“…However, the same trial found that there was a modest detrimental effect in patients not receiving respiratory support, again highlighting the importance of appropriate balance in the inflammatory response to COVID-19. In patients with diabetes, corticosteroids can have an impact on glycaemic control and other metabolic parameters and their use should be under careful clinical review ( 303 ).…”
Section: Key Factors In the Interplay Between Covid-19 And Diabetesmentioning
confidence: 99%
“…This emphasizes the presence of strong interactions between (SARS-CoV-2 + dexamethasone). The output of literature survey over clinical trials of umifenovir (Lian et al 2020;Vankadari 2020;Choudhary and Silakari 2020;Costanzo et al 2020;Zhang et al 2020;Kadam and Wilson 2017;Valle et al 2020)/dexamethasone (Ortolani and Pastorello 2020;Li and De Clercq 2020;Mittal et al 2020;Ledford 2020; Low-cost dexamethasone 2020; WHO welcomes preliminary Alessi et al 2020;Cain and Cidlowski 2020;Lammers et al 2020;Stauffer et al 2020) on SARS-CoV-2 infected patients also suggests that dexamethasone is the best and the first approved referral drug in UK, Australia, and South Africa countries for the treatment of COVID-19 infection. Thus, dexamethasone is one of the best-repurposed drugs to bind SARS-CoV-2 over umifenovir.…”
Section: Interactions Present In Sars-cov-2 + Dexamethasone/umifenovirmentioning
confidence: 99%
“…Based on positive results, dexamethasone has been authorized by the UK government for the treatment of critically ill COVID-19 patients (53). However, the comorbidity factors (especially diabetes) should be considered before treatment because some researchers reported that dexamethasone increases the risk of COVID-19 progression to severe disease, especially in patients with diabetes (54,55).…”
Section: Modern Treatmentmentioning
confidence: 99%